The Social Construction of Unregistered Marriage Through Legal Policy and Societal Experience: A Bibliometric Approach - Kauli, Ilham; Oman Sukmana; Rachmad K. Dwi Susilo (International Journal of Education, Vocational and Social Science, 2025)
Unregistered marriage (pernikahan siri) is a complex social phenomenon in Indonesia, influenced by religious norms, cultural traditions, and legal policies. Although Indonesia’s Marriage Law No. 1 of 1974 mandates the official registration of marriages, pernikahan siri continues to be practiced for various reasons, including economic and administrative factors. This study aims to analyze the social construction of pernikahan siri using a bibliometric approach with VOSviewer. By applying the PRISMA protocol, this research identifies research trends, collaboration networks, and dominant themes in the relevant literature. Out of 63 articles retrieved from Google Scholar (2016–2024), 25 relevant articles were analyzed in depth. The findings reveal that pernikahan siri is predominantly studied in the context of marriage law (31%), Islamic law (21%), and women's rights (8%). Furthermore, the study highlights that inconsistencies in legal policies and the lack of sanctions for offenders contribute to the persistence of pernikahan siri in society. By examining the social construction of pernikahan siri from legal and societal perspectives, this research contributes to identifying research gaps and informing more effective policy directions.